2016
DOI: 10.2967/jnumed.115.171389
|View full text |Cite
|
Sign up to set email alerts
|

Anti-3-18F-FACBC (18F-Fluciclovine) PET/CT of Breast Cancer: An Exploratory Study

Abstract: The purpose of this study was to explore the uptake of the synthetic amino acid analog PET radiotracer anti-3-18 F-FACBC ( 18 F-fluciclovine) in breast lesions with correlation to histologic and immunohistochemical characteristics. Methods: Twelve women with breast lesions underwent 45-min dynamic PET/CT of the thorax after intravenous administration of 366.3 ± 14.8 (337.44-394.05) MBq of 18 F-fluciclovine. Uptake in the primary lesions at 4 representative time points (5, 17, 29, and 41 min) after injection we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…Because amino acid transport is upregulated in many types of cancer, 18 F-fluciclovine has potential application in multiple types of cancer. In this issue of The Journal of Nuclear Medicine, 2 groups report promising preliminary results for FACBC in women with breast cancer naïve to therapy (2,3). These studies demonstrated substantially higher uptake of 18 F-fluciclovine in primary and metastatic breast cancers than in benign breast lesions and normal breast tissue.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Because amino acid transport is upregulated in many types of cancer, 18 F-fluciclovine has potential application in multiple types of cancer. In this issue of The Journal of Nuclear Medicine, 2 groups report promising preliminary results for FACBC in women with breast cancer naïve to therapy (2,3). These studies demonstrated substantially higher uptake of 18 F-fluciclovine in primary and metastatic breast cancers than in benign breast lesions and normal breast tissue.…”
mentioning
confidence: 88%
“…The report from the Emory group, by Tade et al (2), evaluated 18 F-fluciclovine PET/CT in 12 women with malignant (n 5 13) and benign (n 5 4) breast lesions with histologic verification. In this study, patients underwent dynamic 18 F-fluciclovine PET/CT of the thorax for 45 min.…”
mentioning
confidence: 99%
“…Anti-3-[ 18 F]-FACBC (7) was shown to be more efficacious than [ 111 In]-Prostascint in detecting recurrent prostate cancer and has recently been approved by the FDA as Axumin for prostate cancer. In a series of preliminary studies in humans, anti-3-[ 18 F]FACBC (7) was observed to show increased uptake in lung, 98 breast, 99,100 and renal 101 lesions, whereas anti-2-[ 18 F]FACPC (12) showed uptake in metastatic prostate cancer. 102,103 The transport mechanism of the AAs anti-3-FACBC (7) has been elucidated in human prostate cancer 17,18,[104][105][106][107] and glioma 105 cells.…”
Section: Iodinated α α-Dialkyl Amino Acidsmentioning
confidence: 99%
“…Not all tumors are intensely FDG avid such as lobular breast cancer and bronchio alveolar cancer of the lung and it would be difficult to implement FDG PET/CT based early therapy assessment for these cancers. However, a novel PET radiopharmaceutical such as FACBC(18), which demonstrates intense uptake in lobular breast cancer can be successfully deployed. Therefore, selecting a tumor type or molecular subtype, which has moderate to intense avidity for the PET radiopharmaceutical, is fundamentally important.…”
Section: (C) Early Therapy Assessmentmentioning
confidence: 99%